Heart Failure and Stroke Risk in Atrial Fibrillation: Temporal Trends From a Nationwide Cohort Study - Eero Jalli; Ville Langén; Jussi Jaakkola; K. E. J. Airaksinen; Olli Halminen; Jukka Putaala; Pirjo Mustonen; Jari Haukka; Juha Hartikainen; Miika Linna; Mika Lehto; Konsta Teppo (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Heart failure (HF) is a well‐recognized risk factor for ischemic stroke (IS) in patients with atrial fibrillation (AF). Advancements in medical research have significantly improved the detection and management of both AF and HF. However, limited data are available on whether these changes have modified the stroke risk associated with HF in patients with AF. This nationwide retrospective cohort study aims to evaluate temporal trends in HF‐related IS risk among patients with AF. Methods The FinACAF (Finnish AntiCoagulation in Atrial Fibrillation) registry‐linkage study includes all patients in Finland with incident AF from 2007 to 2018. Results We identified 229 565 patients with incident AF of whom 17.4% had HF at the time of AF diagnosis. Crude IS rates decreased both in patients with and without HF over the study period. HF was independently associated with a 30% to 50% higher IS rate in 2007 to 2010, but this association attenuated to only 10% to 15% higher in 2015 to 2018. This reduction in HF‐related stroke risk was observed primarily in patients without a history of myocardial infarction (MI) (incident rate ratio in 2015–2018, 1.08 [95% CI, 0.95–1.22]), while stroke risk associated with HF remained unchanged in patients with prior MI (incident rate ratio during the entire study period, 1.23 [95% CI, 1.07–1.41]). Conclusions Stroke risk associated with HF has decreased among patients with AF, driven by a decline in HF‐related stroke risk in patients without a history of MI. However, HF remains an important stroke risk factor in patients with AF with a history of MI.